Performance of concentrated cropmax on growth and yield of mungbean - Shimu, LA; Hasan, MM; Khan, ABMMM; Hossain, MK; Howlader, MHK (Progressive Agriculture, 2018)
The present study was conducted at the research field of Patuakhali Science and Technology University (PSTU), Patuakhali during the period from December 2013 to March 2014 to study on the effect of a concentrated fertilizer (Cropmax) on the growth and yield the Mung bean. It also observed the comparative growth and yield performance of foliar application Cropmax ( 0, 2.0, 3.0 and 5.0 ml L–1) . Data were collected on plant height, leaf per plant, branches per plant, length of root, leaf area, dry weight of shoot, dry weight of root, TDM, AGR, CGR and RGR, number of pod per plant, pod length, number of seed per pod, thousand seed weight, grain yield (t ha–1), straw yield (t ha–1), biological yield (t ha–1) and harvest index (%) etc.The experiment was laid out in a completely randomized block design (RCBD) with three replications. The collected data were analyzed statistically and means were adjudged by DMRT at 5% level of probability. The treatments Cropmax @ 3.0 ml L–1 as foliar application gave the highest performance in respect of all growth and yield parameters. Progressive Agriculture 29 (3): 239-247, 2018